The Use of Metals in the Voltaic Series and Its Implications on How Natural Batik Dye is Fixed - Maghfiroh, Maghfiroh; Nugraheni, DIan; Widadi, Zahir; Murty, Daru Anggara; Fahria, Mila; Pratiwi, Novida (Department of Chemistry Faculty of Science and Technology Walisongo, 2023)
The presence of natural colorants in the batch industry supports efforts to create sustainable products. However, the disadvantage of natural coloring substance is that tissue fibers generally have a low affinity to the pigment components, so the natural colorant is easily flourishing. This fact is based on exploring natural coloring substances and the type of fixator of the corresponding natural coloring substance. In addition to strengthening the absorption of color substances into the fiber, the fixator also serves to know the direction of color produced by the natural coloring substance. In testing, fixers are used that contain metals present in voltaic series. The object of the study is to described the color characteristics produced by natural dyeing substances (secang and tegeran woods) on various types of fixers that are included in the voltaic series. Color quality is assessed from 3 aspects i.e. color intensity parameters visually, color resistance with grey scale and color direction with website coolors.co. In general, the secang wood produces the pink color (warm category) while the tegeran wood color is yellow (vintage category). There is a regular sequence of the color concentration of the fabric achieved by each voltaic series metal used as a fixer. If the metal is applied as a fixer to the natural coloring material, the stronger oxidative properties of a metal on the voltaic series, the older the resulting color will be.